The Determinants of Going Concern Audit Opinions: Evidence from Shanghai Stock Exchange over 2009 to 2011 - LIU, LUPING (2012)
This research examines the factors which can affect auditors to issue going concern audit opinions in the Chinese stock market, and furthermore, to discuss the audit quality among Chinese reporting system through the issuance of going concern opinions. Firstly, the data results illustrate that Chinese auditors are more likely to issue going concern audit opinions to those listed companies with poor profitability, low liquidity, less cash inflows and high leverage. Secondly, it can be examined that audit fee paid by a client has no statistically significant effect on impacting auditors to give going concern audit opinions. Finally, comparing with Big-Four and non-Big four audit firms, no significant difference between two types of auditors on which one have more preference to issue going concern audit opinions is found. Generally, the research shows a mature audit profession in developing countries like China is being formed, that audit independence is not compromised by economic dependence and the majority of Chinese auditors mainly issue going concern opinions based on financial distress indicators. Besides, this research paper indicates additional discussion about improvements on audit quality and independence since the new audit standard for going concern is promulgated in 2003.